Factors affecting scrotal measurements and weight of Ouled Djellal rams in eastern and south-eastern Algeria - Allaoui A.; Safsaf B.; Djaalab I.; Laghrour W.; Tlidjane M. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
Improving the reproductive capacity of rams spawning through selecting those with the best performance. The aim of our study was to evaluate some of these performances in rams bred Ouled Djellal. Twenty one Ouled Djellal rams divided equally into three age groups (group I: 2-3 years; group II: 4 years; group III: 5-6 years) were followed at Bouchebaa’s pilot farm in Constantine, and 07 lambs, at the Artificial Insemination Centre at Biskra. For all these males we have monthly determined: the antero-posterior diameter of the testis, right and left ; the perimeter of the scrotum, scrotal volume, and body weight. In young rams, it was observed: (i) increased values of weight and scrotal measurements significant (p <0.01 to p <0.001) for periods “spring vs summer“ and “spring vs autumn and a slight decrease (not significant, p>0.05) in winter; and (ii) a highly significant positive correlation between the different weight and scrotal measurements, and no significant difference between measures of left and right testicles. In adult rams a highly and significant positive correlation appears between body weight and scrotal measurements for age groups 2-3 years and 4 years. But this correlation is insignificant for the third group (5-6 years). Regarding the age effect on the evolution of weight and scrotal measurements, we find a variation ranging from very (p <0.01) at highly (p <0.001) significant between the age groups 2-3 vs 4 years, and 2-3 vs 5-6 years against any change significant of these parameters appears between ages 4 vs 5-6 years. This study shows that there is a positive correlation between the measurements of the gonads and body weight that is in decline with age, and that these measurements in adults reach their peak around the age of 4 years, then stabilized relatively thereafter.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)